Семантический сдвиг глагола при двуязычии - Пажусис, Л. (Kalbotyra, 1979)
Little attention has so far been devoted to the description of semantic extensions due to the mechanism of substitution (E. Haugen) (i. e. the introduction into L1 discourse of L2 distributions, in N. Hasselmo’s definition) under bilingualism, especially when they are based on the similarity of L1 and L2 lexical items. In measurement of total linguistic interference. synonymous extension is no less important than importation (i. e. the introduction into L1 discourse of L2 identities). In this respet, the verb, as the dominant structural element of the sentence, deserves particular attention. because the interdependence of semantics and syntax becomes basic to the linguistic model of its description.A study of the linguistic corpus elicited from the Lithuanian periodicals published in the USA and Canada by actual immigrants whose primary language (L1) has for several decades been in contact with American English (L2) yields the following generalizations:1. If we assume that a semantic change of the verb and a change or its semantic combinability are interdependent, semantic interference of the L2 verb must be generally viewed as a semantic change or redistribution of the synonymous L1 verb through the mechanism of introduction into L1 discourse of L2 distributions.2. Synonymous extension of meaning or redistribution of the L1 verb evolves within the ‘contrastive gap’ between the synonymous L1 and L2 verbs.3. Semantic interference of the L2 verb manifests itself not only by removing the combinatorial semantic restrictions which are valid for the verb and the noun in L1 and thus extending the previous semantic similarity between L1 and L2 verbs to fuller congruence, but also by imposing constraint on the selection of L1 verbs and thus obliterating some L1 verbs semantically related with the one experiencing extensions.4. Semantic interference of the L2 verb may manifest itself by reinforcing some redistributions of indigenous verbs current in L1 before immigration, but rejected as archaic and/or alien by the present-day L1 norm in the home country.